VisiUMouse: An Ubiquitous Computer Vision Technology for People with Motor Disabilities - Xavier, Krishna Ferreira; Costa, Vinícius Kruger da; Cardoso, Rafael Cunha; Peroba, Jamir Alves; Ferreira, Adriano Oliveira Lima; Machado, Marcelo Bender; Tavares, Tatiana Aires; Rodrigues, Andréia Sias (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2017: Anais Estendidos do XXIII Simpósio Brasileiro de Sistemas Multimídia e Web, 2017)
VisiUMouse is a solution that enables accessibility to computer’s use by people with upper limbs motor disability. This Assistive Technology uses the concepts of Computational Vision to recognition and face tracking, using the eye as reference point. Through video input, that tracks the eye movement, we control the mouse cursor by webcam, providing an amplification in the functional abilities of these users and, consequently, promoting inclusion. The VisiUMouse was evaluated following the Fitts’s law protocol, which involves common pointing, select and click tasks, used as metrics to verify interaction with the computer. KEYWORDS Computer Vision, Assistive Technology, VisiUMouse, Accessibility, Ubiquitous Technology, OpenCV, Face Tracking